Aktivitas Antibakteri Minyak Atsiri Kulit Jeruk Limau (Citrus amblycarpa (Hassk.) Ochse) Dalam Mengendalikan Bakteri Streptococcus mutans: Antibacterial Activity of Citrus Limau Atsir Oil (Citrus amblycarpa (Hassk.) Ochse) in Controlling Streptococcus mutans - Muhammad Junaedi (Bioma, 2022)
Dental caries is an infection disease of tooth tissue caused by Streptococcus mutans bacteria. Atsiri is essential oil is a liquid-shaped compound that is thought to have potential as an antibacterial. The purpose of this study was to determine the antibacterial potential of essential oil of limau lime in controlling Streptococcus mutans bacteria. The antibacterial test in this study used disk disfussion method with 8 treatment groups and 4 replications is 5 concentrations of atsiri oils, 1 positif disc amoxicillin antibiotic, 2 negative control with DMSO and aquades. The data obtained were analyzed with normality test, Anova test and BNT test. Isolation of atsiri’s oil of limau lime in this study using the method of steam-water distillation. Streptococcus mutans bacteria were isolated from dental caries patients and tested using macroscopic, microscopic, gram staining, and biochemical methods. The study found that the atsiri oils of limau lime has antibacterial activity in vitro against Streptococcus mutans bacteria, as evidenced by the formation of an inhibit zone. Concentration as 100% with 15.38mm inhibitory zone diameter is the most effective concentration to inhibit the growth of Streptococcus mutans bacteria. The statistical analysis revealed a significant influence between the treatments at the 5% significance level.